Unilateral Pedicled Pectoralis Major Harvested by Endoscopic-Assisted Method Achieves Adequate Management of Sternal Infection and Mediastinitis - Lin, Chih-Hung; Lin, Cheng-Hung; Tsai, Feng-Chun; Lin, Pyng-Jing (Journal of Reconstructive Microsurgery, 2019)
Background Bilateral PM muscles or combination with rectus abdominis or omentum are commonly used for upper and lower sternal wound infections. Unilateral PM harvesting using endoscopic-assisted method may have a simple, safe, and reliable entire muscle harvesting with comparable result of less donor-site violation.Methods A retrospective review was performed from 2003 till 2015 on 38 patients referred to a single plastic surgeon for treatment of sternal wound infection following median sternotomy for cardiovascular surgery. After the humerus insertion of PM was cut with the assistance of endoscope visualization, all the other PM insertions on the sternum, rib, and clavicle were divided, the unilateral pedicled PM can be advanced approximately 10 cm to cover the cephalad and caudal sternum, and fill the retrosternal mediastinum.Results Four re-explorations in three patients for postoperative hematoma occurred. No early recurrent infection for wound dehiscence experienced. Three patients died of multiple organs failures as 30-day mortality. Two patients underwent late recurrent infections; one patient had twice wire infection removals at 4 and 6 months after transfer, and the other had another PM for rib osteomyelitis in 3 years.Conclusion Unilateral PM transfer is justified to provide a simple, reliable, straightforward procedure for sternal infection management and mediastinal obliteration without violation of second flap in compromised patients.
Keywords: pedicled pectoralis; endoscopic; sternal infection and mediastinitis